Properties Of Organosilica Encapsulated Dye For Bioimaging Application - Tamezer, Abdul Halim Mohd (Universiti Sains Malaysia, 2017)
In this work silica nanoparticles (SiNPs) colloids were synthesized by using micelle formation approach. The volume of 2-butanol co-solvent was varied from 2, 4 and 6 ml. Particle sizes were observed from TEM increased from 30.46, 34.354, and 42.47 nm with increasing amount of 2-butanol from 2, 4 and 6 ml respectively. The effect of D-glucose and trisodium trimetaphosphate (TSTMP) as excipient mixture on filtration efficacy was studied. This excipient addition is supposed to provide additional biological coating on the silica surface that enhances stability and biocompatibility for in vitro analysis. Filtration efficacy after the addition of TSTMP showed higher volume of 2-butanol gave lower filtration efficacy compared to smaller volume (98.03% - 89.82%). In this study, Nile red dye was used as a dye model to produce silica encapsulated Nile red dye (SiNR). The stability of SiNR of various sizes in sodium chloride (NaCl) solution and mouse serum volume rates were analysed. As the concentration of NaCl increased, the stability efficiency decreased. Similar result was obtained for stability of SiNR in mouse serum, where by the stability of SiNR decreased with increasing the concentration of mouse serum.The optimum stability of SiRN was obtained was volume of 4 ml of 2-butanol.In biological medium, the stability efficiency of SiNR in NaCl with concentration of 0.1, 0.5 and 1.0 M are 57.7%, 56.05 and 55.6% respectively and stability of SiNR in mouse serum concentration of 5, 10 and 25% are 58.9, 51.7 and 34.3% respectively. Decolorization efficiency of SiNR produced using 4 ml of 2-butanol is lower (27.25%) compared to SiRN produced using 2 and 6 ml of 2-butanol.